Carbon, sulfur and nitrogen oxide emissions from combustion of pulverized raw and torrefied biomass. (15th January 2017) - Ren, Xiaohan; Sun, Rui; Meng, Xiaoxiao; Vorobiev, Nikita; Schiemann, Martin; Levendis, Yiannis A.
Abstract: This work contrasted gaseous emissions of carbon, sulfur and nitrogen oxides from combustion of several types of biomass including woody, herbaceous and crop-derived wastes, pulverized in the size range of 75–150 μm. Both raw and torrefied biomass were exposed to high heating rates (10 4 –10 5  K/s) in a laboratory-scale electrically-heated drop-tube furnace, operated at 1400 K. Combustion occurred under fuel-lean conditions. Torrefied biomass has lower volatile matter content, higher fixed carbon content and higher heating value than raw biomass. Results revealed that (a) CO2 emission factors from torrefied biomass were higher than those from raw biomass, reflecting the higher carbon content of the former, however there was no uniform trend in emission factors (kg/GJ); (b) SO2 emission factors of torrefied biomass were lower than those from raw biomass, even if some torrefied biomass types contained higher sulfur mass fractions than their raw biomass precursors. All raw and torrefied biomass, with one exemption, generated lower SO2 emission factors than a typical sub-bituminous coal; (c) torrefied biomass has higher fuel-nitrogen mass fractions than their raw biomass precursors; however, there was no clear trend in NOx emission factors between raw and torrefied biomass, as torrefied herbaceous and woody biomass types generated higher while torrefied crop biomass types generated lower emission factors than their raw biomass precursors. Comparing with the sub-bituminous coal, some raw and torrefied biomass types generated lower and some higher NOx emission factors. Overall, combustion of most types of biomass, either in raw or torrefied state, can result in lower SO2 and NOx emissions factors than those of typical western US sub-bituminous coals while, in principle, generating minimal net emissions of carbon.